Analisis Hukum Islam terhadap Praktik Nikah Siri di Indonesia: Studi Kritis atas Aspek Legalitas, Perlindungan Hak Perempuan, dan Dampaknya terhadap Tatanan Sosial - Simbolon, Muhammad Iran; Ridwan, M Sulaiman (EL-EMIR Institute, 2025)
This study aims to: (1) assess the legality of nikah siri—unregistered marriages—under classical Islamic jurisprudence (fiqh) and Indonesian statutory law; (2) determine the extent to which women’s rights are protected or neglected; and (3) analyze the practice’s impact on the social order, particularly children’s legal status, family structure, and public perceptions of legal authority. The research adopts a qualitative design with a normative-empirical legal approach. Primary data were gathered through a literature review (covering the four Sunni schools of fiqh, fatwas of the Indonesian Council of Ulama, the Indonesian Marriage Law No. 1/1974 as amended by Law 16/2019, the Compilation of Islamic Law, and Supreme Court decisions) and in-depth interviews with 20 women who had experienced nikah siri in the provinces of Riau, West Java, and West Nusa Tenggara. Data were analyzed using the maqāṣid al-sharīʿah framework to evaluate public welfare (maṣlaḥah) and feminist-legal theory to map gender vulnerabilities. Source and method triangulation ensured data validity. Findings indicate that, although nikah siri is deemed valid in fiqh when all pillars and conditions of marriage are met, the lack of official registration creates legal uncertainty for wives and children in matters of inheritance, maintenance, and civil administration. Field evidence confirms significant social risks, including stigmatization, restricted access to public services, and the economic marginalization of women. The study recommends harmonizing state and Islamic law by mandating marriage registration—grounded in the protective principles of ḥifẓ al-nafs (safeguarding life) and ḥifẓ al-nasl (safeguarding lineage)—and strengthening community education to realize the objectives of Sharia and substantive justice.